Exosomes and Biomaterials: In Search of a New Therapeutic Strategy for Multiple Sclerosis - Doddy Denise Ojeda-Hernández; Mercedes A. Hernández-Sapiéns; Edwin E. Reza-Zaldívar; Alejandro Canales-Aguirre; Jordi A. Matías-Guiu; Jorge Matías-Guiu; Juan Carlos Mateos-Díaz; Ulises Gómez-Pinedo; Francisco Sancho-Bielsa (Life, 2022)
Current efforts to find novel treatments that counteract multiple sclerosis (MS) have pointed toward immunomodulation and remyelination. Currently, cell therapy has shown promising potential to achieve this purpose. However, disadvantages such as poor survival, differentiation, and integration into the target tissue have limited its application. A series of recent studies have focused on the cell secretome, showing it to provide the most benefits of cell therapy. Exosomes are a key component of the cell secretome, participating in the transfer of bioactive molecules. These nano-sized vesicles offer many therapeutical advantages, such as the capacity to cross the blood-brain barrier, an enrichable cargo, and a customizable membrane. Moreover, integrating of biomaterials into exosome therapy could lead to new tissue-specific therapeutic strategies. In this work, the use of exosomes and their integration with biomaterials is presented as a novel strategy in the treatment of MS.